Broadcasting in the shadow of power: regulatory challenges and political violations during Indonesia’s 2024 election - Sulistijanto, Andi Budi; Abdurrahman, Muhammad Sufyan; Putra, Dedi Kurnia Syah (Frontiers in Communication, 2025)
Amid intensified political competition during Indonesia’s 2024 General Election, this study examines how broadcasting regulators enforced ethical standards under structural, commercial, and ideological pressures. Using a qualitative case study method, it draws from institutional documents, official reports, and interviews with broadcasting practitioners in West Java to analyze the challenges faced by the Indonesian Broadcasting Commission (KPI) and its regional counterparts (KPID) in maintaining media neutrality. Findings show that politically biased content and premature campaign materials were frequently aired by national broadcasters, often influenced by partisan ownership and central editorial control. Local stations lacked authority to intervene, as the National Network System (SSJ) limited regional oversight and contributed to inconsistent enforcement. Regulatory actions were largely reactive, relying on post-violation warnings rather than proactive prevention. The study applies critical media theories to reveal how market competition, structural asymmetries, and blurred boundaries between journalism and political promotion undermine regulatory independence. It concludes that Indonesia’s current broadcast regulation system remains vulnerable to media oligarchy and lacks the institutional resilience needed to protect democratic communication. To address these challenges, urgent reforms are recommended in legal authority, transparency, and civic engagement. This research contributes to broader debates on media governance and electoral integrity in hybrid media environments.